2013
DOI: 10.1021/np4005745
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase and HDAC Inhibitors from the Endophytic Fungus Epicoccum nigrum

Abstract: A chemical investigation of the endophytic fungus Epicoccum nigrum isolated from leaves of Mentha suaveolens collected in Morocco resulted in the isolation of five new polyketides, epicocconigrones A and B (1 and 2), 3-methoxyepicoccone B (3), 3-methoxyepicoccone (4), and 2,3,4-trihydroxy-6-(methoxymethyl)-5-methylbenzaldehyde (5), together with five known compounds (6-10). The structures of the new compounds were unambiguously determined by extensive analysis of the 1D and 2D NMR and mass spectroscopic data. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(63 citation statements)
references
References 47 publications
(99 reference statements)
1
60
0
Order By: Relevance
“…The characterization of 3-8 suggested that the aldehyde substrate of the PS reaction could be flavipin, which has been reported from some fungal cultures (28)(29)(30)(31)(32)(33). To confirm the postulation, C. globosum 1C51 was fed with sodium [1-13 C]-, [2-13 C]-, and [1,2-13 C 2 ]-acetates, respectively, to lead to the expected 13 C enrichment of the 4,5,6-trihydroxyisoindolin-1-one motif of chaetoglines E (5) and F (6), but not the aromatic methyl carbons (C-22 in 5 and C-21 in 6), whose intensity could only be enhanced by supplementing the fungal culture with L-[methyl-13 C]-methionine (SI Appendix, Tables S9 and S10).…”
Section: (C-23)mentioning
confidence: 57%
See 1 more Smart Citation
“…The characterization of 3-8 suggested that the aldehyde substrate of the PS reaction could be flavipin, which has been reported from some fungal cultures (28)(29)(30)(31)(32)(33). To confirm the postulation, C. globosum 1C51 was fed with sodium [1-13 C]-, [2-13 C]-, and [1,2-13 C 2 ]-acetates, respectively, to lead to the expected 13 C enrichment of the 4,5,6-trihydroxyisoindolin-1-one motif of chaetoglines E (5) and F (6), but not the aromatic methyl carbons (C-22 in 5 and C-21 in 6), whose intensity could only be enhanced by supplementing the fungal culture with L-[methyl-13 C]-methionine (SI Appendix, Tables S9 and S10).…”
Section: (C-23)mentioning
confidence: 57%
“…The observation, along with their 1 Hand 13 C-NMR spectra, suggested that the latter was a methyl ester of the former. Scrutiny of the 1 H-1 H COSY, ROESY, HSQC, and HMBC spectra of 3 indicated the presence of a 4,5,6-trihydroxy-7-methylisoindolin-1-one motif (27,28), which was shown to share the nitrogen atom with the 1-MT moiety (SI Appendix, Fig. S9).…”
Section: (C-23)mentioning
confidence: 99%
“…A preliminary structure-activity relationship proposal suggested that a β-hydroxyl-α,β-unsaturated carbonyl moiety, present in 82, 84, and 86 but absent in inactive compounds (83 and 85), is necessary for the inhibition of protein kinases. Compound 82 showed also strong inhibition against histone deacetylase (HDAC), becoming a promising compound for the development of anticancer drugs [53].…”
Section: Novel Metabolites With Biological or Chemical Relevancementioning
confidence: 99%
“…One strategy to overcome these obstacles is to focus on new or less investigated habitats such as arctic glaciers or antarctic dry valleys, 10 deserts, 11 salt lakes 12 or endophytic and sponge-associated fungi. [13][14][15] Schulz et al hypothesized that ecological niches and a high metabolic interaction (e.g. with plants in the case of endophytic fungi) will yield higher proportions of fungi that are capable of producing new metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…16 Other approaches for enhancing the chemical diversity of fungal products include the "one strain -many compounds" (OSMAC) strategy, 17-19 mixed fermentations (also called co-cultivation) of several microorganisms [20][21][22][23] or the use of epigenetic modifiers. 24,25 In our ongoing search for new bioactive compounds from fungi, 15,26,27 we investigated the fungus Gymnascella dankaliensis, which was isolated from a soil sample in the vicinity of the Giza pyramids, Egypt. Bioassay-guided fractionation of the extract following cultivation on solid rice medium yielded four new natural products (1 -4), as well as six known compounds (5 -10).…”
Section: Introductionmentioning
confidence: 99%